2015
DOI: 10.4103/2224-3151.206623
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of household drinking-water contamination and of acute diarrhoeal illness in a periurban community in Myanmar

Abstract: The prevalence of acute diarrhoea reported for children under 5 years was high and a high level of drinking-water contamination was detected, though it was unclear whether this was due to contamination at source or at point-of-use. Maintenance of drinking-water quality in study households is complex. Further research is crucial to prove the cost effectiveness in quality improvement of drinking water at point-of-use in resource-limited settings. In addition, empowerment of householders to use measures of treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…19 From the neighboring country Myanmar, a study reported that at point of use 94% of the water samples contain feacal coliforms and the prevalence of ADD among children were 156/1000, less than our study. 25 As reported by many studies from developing countries our study also found that the relation between water quality at the source and WBD was lower than sanitation and treatment at point of use. 5,6,7,19 WHO criteria for safe water accessibility include improved water, equated it as safe.…”
Section: Discussionsupporting
confidence: 80%
“…19 From the neighboring country Myanmar, a study reported that at point of use 94% of the water samples contain feacal coliforms and the prevalence of ADD among children were 156/1000, less than our study. 25 As reported by many studies from developing countries our study also found that the relation between water quality at the source and WBD was lower than sanitation and treatment at point of use. 5,6,7,19 WHO criteria for safe water accessibility include improved water, equated it as safe.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with our finding, the microbiological quality of drinking water in the Rift Valley area of Ethiopia has been reported as very poor (Amenu et al 2014 ). Furthermore, a study in Myanmar revealed that 94% of household-stored drinking water samples were contaminated with thermotolerant coliforms (Myint et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] The indicator of improved drinking water is good (82.5%) and comparable to other studies as well. [ 7 ] However, the piped water connection was lesser as compared to the national figures. [ 8 ] Besides, due to better or improved drinking water sources, so there was a decreased burden of water-borne diseases, especially among children.…”
Section: Discussionmentioning
confidence: 99%